EDGE2D-EIRENE modelling of near SOL Er: possible impact on the H-mode power threshold. (9th March 2017) - Chankin, A V; Delabie, E; Corrigan, G; Harting, D; Maggi, C F; Meyer, H
Abstract: Recent EDGE2D-EIRENE simulations of JET plasmas showed a significant difference between radial electric field ( E r ) profiles across the separatrix in two divertor configurations, with the outer strike point on the horizontal target (HT) and vertical target (VT) (Chankin et al 2016 Nucl. Mater. Energy, doi:10.1016/j.nme.2016.10.004 ). Under conditions (input power, plasma density) where the HT plasma went into the H-mode, a large positive E r spike in the near scrape-off layer (SOL) was seen in the code output, leading to a very large E × B shear across the separatrix over a narrow region of a fraction of a cm width. No such E r feature was obtained in the code solution for the VT configuration, where the H-mode power threshold was found to be twice as high as in the HT configuration. It was hypothesised that the large E × B shear across the separatrix in the HT configuration could be responsible for the turbulence suppression leading to an earlier (at lower input power) L–H transition compared to the VT configuration. In the present work these ideas are extended to cover some other experimental observations on the H-mode power threshold variation with parameters which typically are not included in the multi-machine H-mode power threshold scalings, namely: ion mass dependence (isotope H–D–T exchange), dependence on the ion ∇ B drift direction, and dependence on the wall material composition (ITER-like wall versus carbon wall in JET). In all these cases EDGE2D-EIRENE modelling shows larger positive E r spikes in the near SOL under conditions where the H-mode power threshold is lower, at least in the HT configuration.